Lipids, Safety Parameters, and Drug Concentrations After an Additional 2 Years of Treatment With Anacetrapib in the DEFINE Study. (November 2014) - Gotto, Antonio M.; Kher, Uma; Chatterjee, Manash Shankar; Liu, Yang; Li, Xiujiang Susie; Vaidya, Sanskruti; Cannon, Christopher P.; Brinton, Eliot A.; Moon, Jennifer E.; Shah, Sukrut; Dansky, Hayes M.; Mitchel, Yale; et al.
Anacetrapib is a cholesteryl ester transfer protein (CETP) inhibitor that has previously been shown to reduce low-density lipoprotein cholesterol (LDL-C) and raise high-density lipoprotein cholesterol (HDL-C) in patients with or at high risk of coronary heart disease in the 76-week, placebo-controlled, Determining the Efficacy and Tolerability of CETP Inhibition with Anacetrapib (DEFINE) trial. Here, we report the results of the 2-year extension to the DEFINE study where patients (n = 803) continued on the same assigned treatment as in the original 76-week study. Treatment with anacetrapib during the 2-year extension was well tolerated with a safety profile similar to patients on placebo. No clinically important abnormalities in liver enzymes, blood pressure, electrolytes, or adverse experiences were observed during the extension. At the end of the extension study, relative to the original baseline value, anacetrapib reduced Friedewald-calculated LDL-C by 39.9% and increased HDL-C by 153.3%, compared to placebo. The apparent steady state mean plasma trough concentration of anacetrapib was ∼640 nmol/L. Geometric mean plasma concentrations of anacetrapib did not appear to increase beyond week 40 of the 2-year extension of the 76-week DEFINE base study. In conclusion, an additional 2 years of treatment with anacetrapib were well tolerated with durable lipid-modifying effects on LDL-C and HDL-C.